Migration, openness and the global preconditions of "smart development" - Arno Tausch; Almas Heshmati (Institute for the Study of Labor (IZA), 2011)
In this article, we present a first empirical reflection on 'smart development', its measurement, possible 'drivers' and 'bottlenecks'. We first provide cross-national data on how much ecological footprint is used in the nations of the world system to 'deliver' a given amount of democracy, economic growth, gender equality, human development, research and development, and social cohesion. To this end, we first developed UNDP-type performance indicators on these six main dimensions of development and on their combined performance. We then show the non-linear regression trade-offs between ecological footprints per capita on these six dimensions of development and their combined performance index. The residuals from these regressions are our new measures of smart development: a country experiences smart development, if it achieves a maximum of development with a minimum of ecological footprint. We then look at the cross-national drivers and bottlenecks of this 'smart development' and compare their predictive power using stepwise regression procedures. Apart from important variables and indicators, derived from sociological dependency and world systems theories, we also test the predictive power of several other predictors as well. Our estimates underline the enormous importance of the transfer of resources from the center to the periphery, brought about by migration, with huge statistical observed positive effects of received worker remittances on smart human development, Happy Life Years, smart gender justice, smart R&D, and both formulations of the smart development index.
urn:nbn:de:101:1-201201103008
Keywords: C43; F22; F24; Q56; 330; index numbers and aggregation; environment and development; environment and trade; smart development; sustainability; environmental accounts and accounting; environmental equity; population growth; international migration; remittances; Sozialer Indikator; Umweltbelastung; Nachhaltige Entwicklung; Entwicklungsindikator; Außenwirtschaft; Internationale Wanderung; Rücküberweisung (Migranten); Theorie; Welt